The performance of the biological filters in removing the ammonianitrogen from the recirculating system of an intensive freshwater fishpond - Sudin, Rusnani; Jusoh, Ahmad; Ambak, Mohd. Azmi; M., Assaduzzaman (Penerbit Universiti Sains Malaysia, 2004)
Aquaculture is a rapidly developing industry worldwide. It is the best alternative for the decreasing sources of protein supply from sea and river. Heggberget (1996) observed that new technologies have made a rapid increase possible during the last decades, especially in developing countries.